Implementation Of The Scor Digital Standard Method In The Cijurey Dam Package 1 Project - Teddi Apriyadi; Oviyan Patra; Hendy Suryana; Evan Nugraha (Publikasi Indonesia, 2025)
Abstract Dam construction projects face various challenges in supply chain management that can affect the success of the project. This study aims to analyze the implementation of the SCOR Digital Standard (DS) method in improving supply chain performance in the Cijurey Dam Package 1 Project. The research method uses qualitative and quantitative approaches by implementing SCOR Racetrack including the Engage, Define, Analyze, Plan, and Launch stages. The results showed that the baseline performance of RL.2.6 Delivery Performance to Commit Date only reached 73.33% of the target of 90%, Inventory Turnover (ITO) <1.1 times/year of the target ?2 times/year, and Days of Inventory (DOI) reached ±250 days exceeding the maximum target of 180 days. The root of the problem is identified through the 5 Why Analysis and Fishbone Diagram, namely the absence of consignment inventory and regular reconciliation meetings with vendors. The recommended improvement strategies include four improvement projects: Procurement Terms & Conditions Review, Freight Carrier Delivery Performance Evaluation, Regular Reconciliation Meetings, and Consignment Inventory. The implementation of this strategy is projected to increase RL.2.6 to ?90%, reduce the DOI to ?180 days, increase ITO to ?2 times/year, with financial benefits reaching Rp1.29 billion per year.